Data from: Washington, Oregon, and California eelgrass restoration database ... - Ward, Melissa; Beheshti, Kathryn (Dryad, 2023)
Seagrass habitats, which provide essential ecosystem functions such as water quality improvement, biodiversity support, ocean acidification amelioration, and sediment carbon storage, are declining worldwide. Eelgrass (Zostera marina) habitats along the contiguous U.S. west coast are threatened by conflicting human uses and global change, resulting in significant protections and efforts to restore areas where habitat is extant or degraded. Despite a history of eelgrass restoration in this region spanning nearly 60 years, very little work has been published on the subject. Here, we conduct a review of all available literature on eelgrass restoration projects conducted in California, Oregon, and Washington. Of the 82 restoration projects included in this analysis, which occurred from 1989 to 2020, only 6 were published in peer-reviewed journals. Thus, despite the precedent for conducting restoration, a lack of data availability makes assessing regional success, drivers of failure, and best practices extremely ... : Collected via meta-analysis approach - primary and grey literature search. ...